Aero Repair and Overhaul Services at Rolls Royce Group Plc: Application of Activity Based Costing - Vaithiyanathan, Shivany (2005)
In this report an analysis has been carried out to study the application of Activity Based Costing (ABC) to the proposed repair and overhaul process at Rolls Royce Group Plc after the implementation of the aftermarket business policies.